Analisis Pengaruh Belanja Negara, Industri Manufaktur, dan Pendapatan Nasional terhadap Ketimpangan Pendapatan di Indonesia - Suparlan Suparlan; Khaerul Umam (ARZUSIN, 2025)
Income inequality, as reflected by the Gini Ratio, is a key indicator for assessing the fairness of economic distribution, and in Indonesia, its fluctuation over the past decade highlights complex socio-economic dynamics. This study aims to identify the variables influencing changes in the Gini Ratio in Indonesia during the 2014–2023 period. A quantitative approach was applied using secondary data from the Central Statistics Agency (Badan Pusat Statistik) and the Ministry of Finance of the Republic of Indonesia. The research employed multiple linear regression analysis, including classical assumption tests, model feasibility tests, as well as t-tests and F-tests for hypothesis testing. The results indicate that among the three variables examined, only the Manufacturing Industry sector has a significant effect on income inequality, while Government Expenditure and National Income do not show a significant influence. These findings confirm that increases in government spending or national income do not directly reduce income inequality. In contrast, the contribution of the manufacturing sector has been shown to improve income distribution, aligning with previous studies suggesting that growth in this sector positively affects inter-provincial economic equity. The practical implications of these results underscore the importance of inclusive industrialization policies and equitable development of the manufacturing sector across all regions of Indonesia as a long-term strategy to sustainably reduce income inequality.